PENGARUH PENGGUNAAN DIAGNOSIS CHART TERHADAP HASIL BELAJAR MATAKULIAH PRAKTIK DIAGNOSIS SISTEM KELISTRIKAN - Noto Widodo (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThis reserach aims at revealing the influence of the use of diagnose chart toward the learning outcomes among the students of Automotive Engineering Faculty of Engineering Yogyakarta State University on vehicle diagnosis course, especially on electrical part. It covers : (1) the skills to determine problem indication, (2) the identification skills for problem probability, (3) the skills to examine analysis result, (3) the skills in drawing conclusions. This reserach can be catagorized as Non Equivalent Control Group Design. The population was the automotive engineering students who are participated in vehicle diagnosis course on odd semester at academic year of 2012/2013. The research sample was from D1 class as the control group and D2 class as the experimental group. Data gathering techniques was by measuring the learning result from posttest. The obtained data were analyzed from by using independent sample T-Test after the prerequirement test. The research results showed that (1) the use of diagnose chart on vehicle electrical system increased the lerning outcomes (24.31%), and (2) the use of diagnosis chart  on vehicle electrical system increased the students’diagnosis skills, it can be seen from : (a) the improvement of students’ skills to determine problem indication properly with explicit disclosure, (b) the improvement of students’ identification skills for problem probability based on proper logical and theoritical thinking, (c) the improvement of students skill to confirm the analysis results through correct investigation and measurement in a time efficient way, (d) the improvement of students skills in drawing conclusions from their analsysis result.Keywords: diagnose chart, vehicle diagnosis, vehicle electrical system